Rural grocery stores use of communication channels: exploratory study - Brown, Carmen F. (Kansas State University, 2013)
This is an exploratory study looking at the communication channels used in the relationship between rural grocers and rural community members in four Kansas communities. The study is a continuation of research and efforts done by K-State’s Rural Grocery Initiative to help the sustainability of rural grocery stores. This study is looked at through the theoretical lens of uses and gratifications because of the identification of communication channels that satisfy users’ wants and needs. The study is qualitative, using individual interviews to gather data from rural grocers and rural community members. Eight communication channels are identified by the grocers and community members: onsite of grocery store, newspaper (published in a nearby community), mail, radio, website, word-of-mouth, email, and Facebook. The eight communication channels discussed in the study are identified as being beneficial, used, or both by rural grocers and rural community members. The information provided from the study offers suggestions for rural grocers to better reach community members to increase business, and thus increase sustainability in the community.
Keywords: Rural; Grocery stores; Communication channels; Kansas; Mass Communications (0708)